Ulos Batak Sebagai Warisan Budaya Dalam Upacara Adat Di Desa Wisata Huta Nagodang Kecamatan Muara Kabupaten Tapanuli Utara - Jemaya Putri; Harisan Boni Firmando; Rusmauli Simbolon (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The Huta Nagodang tourist village still inherits the traditional Ulos weaving culture which has been preserved from generation to generation from its ancestors until today, namely Ulos Harungguan, which means a collection that includes all types of Ulos. And it has a motif that is combined with the Ulos motif owned by the Toba Batak ethnic group and commodification is carried out as a development of this Ulos. And used as a source of economic income for community members, the Ulos craft from Huta Nagodang village has its own icon which is the only one in Huta Nagodang village which was sacredly inherited from their ancestors as Ulos Harungguan. The aim of this research is to find out Ulos as a cultural heritage in traditional ceremonies in Hutana Godang village, Muara sub-district, North Tapanuli district. The method used in this research uses a qualitative method with a descriptive approach and data collection techniques through observations, interviews with informants, and documentation. The results of this research describe Ulos Batak as cultural heritage in traditional ceremonies involving the village government, traditional leaders and the community.